A proposal for improving sustainability practice through the implementations of reuse and recycle technique in Malaysian construction industry - Wan Nadzri, Osman; Mohd Nasrun, Mohd Nawi; Rohaizah, Saad; Herman Shah, Anuar; Siti Halipah, Ibrahim (American Institute of Physics Inc., 2016)
Construction and demolition waste is often seen as the major contributor to the solid waste stream that is going to landfill, hence, making it the area of focus for improvement. In the construction industry, reuse and recycle principles have been promoted in order to reduce waste and protect the environment. Construction and demolition waste including demolished concrete, bricks and masonry, wood and other materials such as dry wall, glass, insulation, roofing, wire, pipe, rock and soil constitute a significant component of the total waste. Without proper reuse and recycle policies, these construction and demolition wastes would quickly fill all the remaining landfill space, which has already been growing in scarce around this region. Based on the feedback received, on average, a third of respondents said they currently have a lotto benefit from the use of reduce and reuse. In addition, they also agreed that the existing policies help and support the min carrying out the reduce and reuse practices. Respondents also agreed that other stakeholders in the construction industry currently have an excellent awareness in term of implementation of the reduce and reuse in their practices